Tackling the hurdles of electrically pumped colloidal quantum dot lasers - Wang, Yue (2019)
Lasers are devices that produce light by the process of stimulated emission (SE) which amplifies light coherently. They are distinguished from other light sources by their beams with good coherence, directionality, high brightness and spectral purity. As such, lasers have found widespread applications in various fields, including scientific research, industry, medicine and military defense, and actually become ubiquitous in our daily life. Despite of the diversity in laser classification, compact lasers are dominantly made from semiconductors. Especially, electrically driven semiconductor lasers are indispensable components for optical communication. At present, electrically driven semiconductor lasers, or laser diodes, are fabricated by the high-vacuum and high-temperature epitaxy methods, which are not only costly but also difficult to integrate with other optoelectronic devices [1]. As a complement to the epitaxial semiconductor lasers, the cost-effective solution-processed laser diodes have been pursued for the past decades yet demonstrated to be extremely challenging.